2019
DOI: 10.1111/jfs.12753
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antioxidant properties of burgers with quinoa peptide‐loaded nanoliposomes

Abstract: This study was aimed to examine the antioxidant (thiobarbituric acid reactive substances [TBARS], peroxide value [PV], and as well as antimicrobial (total bacterial count, Staphylococcus aureus [S. aureus], mold and yeast counts) activities and spoilage indices (total volatile base nitrogen [TVB‐N]) of quinoa peptide‐loaded liposomes incorporated into burger during 12 days of refrigerated storage. Among four prepared batches, the lowest TBARS, PV, and TVB‐N values (0.281 ± 0.05 mg MDA/kg, 3.25 ± 0.34 mEq/kg an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 76 publications
(102 reference statements)
0
12
0
Order By: Relevance
“…Mahdavi Yekta et al 2019reported that the hydrolyzed quinoa peptides have antioxidant activity. In addition, the encapsulation can increase this property (Mahdavi Yekta et al, 2019). Piñuel et al (2019) reported that the gastric and duodenal hydrolysis of white, red, and black Quinoa showed higher antioxidant activity (Piñuel et al, 2019).…”
Section: 2′-azino-bis 3-ethylbenzothiazoline-6sulfonic Acid (Abts)mentioning
confidence: 99%
“…Mahdavi Yekta et al 2019reported that the hydrolyzed quinoa peptides have antioxidant activity. In addition, the encapsulation can increase this property (Mahdavi Yekta et al, 2019). Piñuel et al (2019) reported that the gastric and duodenal hydrolysis of white, red, and black Quinoa showed higher antioxidant activity (Piñuel et al, 2019).…”
Section: 2′-azino-bis 3-ethylbenzothiazoline-6sulfonic Acid (Abts)mentioning
confidence: 99%
“…Quinoa-based proteins can be considered a rich source of bioactive peptides to which they are attributed important health benefits and strong antioxidant and antimicrobial activities, what was reflected in its incorporation through nanoliposomes in fresh beef burgers [ 79 ]. This is also the case of fish skin peptides, marine byproducts and natural antioxidants, applied as biopreservative through lecithin nanoliposomes in pork patties [ 76 ].…”
Section: Nanoencapsulation Of Bioactive Compounds and Food Ingredimentioning
confidence: 99%
“…Free and encapsulated (nanoliposomes) bioactive peptides obtained from quinoa have been used to increase the shelf-life and quality of burgers [ 127 ]. In this study, the incorporation of bioactive peptides showed a protective effect against lipid oxidation (peroxide and TBARs values) and proteolytic reactions (total volatile basic nitrogen).…”
Section: Application Of Encapsulated Plant-based Active Ingredients In the Meat Industrymentioning
confidence: 99%
“…In this study, the incorporation of bioactive peptides showed a protective effect against lipid oxidation (peroxide and TBARs values) and proteolytic reactions (total volatile basic nitrogen). In addition, microbial assays showed that the quinoa bioactive peptides reduced the total bacterial count and growth of S. aureus , mold, and yeast [ 127 ], which could explain the lowest values of the proteolytic phenomenon in treated burgers. Thus, encapsulation also enhanced the efficacy of bioactive peptides by increasing their antioxidant and antimicrobial properties.…”
Section: Application Of Encapsulated Plant-based Active Ingredients In the Meat Industrymentioning
confidence: 99%